Influence of Different Levels of Fertilizer and Post-Emergence Herbicides on Weed Control Efficiency, Nutrient Depletion by Weeds and Production of Wheat [Triticum aestivum (L.)] - Sarita; Singh, Ishwar; Mehriya, M. L. (International Journal of Bio-resource and Stress Management, 2022)
The field studies were conducted at Instructional Farm, College of Agriculture, Jodhpur (Agriculture University, Jodhpur), Rajasthan, India on Wheat during rabi seasons (November to April) of both the 2018–2019 and 2019–2020. The experiment was consisted of three fertility levels viz., 75% of recommended dose of fertilizer (90-30 kg N-P2O5 ha-1), 100% of RDF (120-40 kg N-P2O5ha-1) and 125% of RDF (150-50 kg N-P2O5 ha-1)] and sub-plots: seven post-emergence herbicides (trisulfuron 15 g ha-1, sulfosulfuron 75%+metsulfuron methyl 5% (ready-mix) 32 g ha-1, clodinafop-propargyl 15%+metsulfuron methyl 1% (ready-mix) 64 g ha-1, carfentrazon 20 g ha-1, metsulfuron methyl 4 g ha-1, weedy check and weed free) in split plot design and replicated thrice. Findings revealed, application of 100% recorded the higher growth attributes viz, plant height, dry matter accumulation (g-2) and leaf area index at 50 DAS, yield parameters viz, effective tillers m-1 row length, and grain, straw and biological yield of wheat over 75% RDF, however it was at par with 125% RDF. Among the post-emergence herbicides, the herbicide clodinafop-propargyl 15%+metsulfuron methyl 1% (ready-mix) 64 g ha-1 significantly increased the growth and yield parameters and yield, while remaining at par with sulfosulfuron 75%+metsulfuron methyl 5% (ready-mix) 32 g ha-1 and proved superior in comparison to rest of the treatments. Maximum nutrients (NPK) depletion by weeds was recorded with the application of 125% RDF. Among herbicides, clodinafop-propargyl 15%+metsulfuron methyl 1% (ready-mix) 64 g ha-1 was also obtained significantly minimum nutrients depletion by weeds.